STRATEGI MEMPEROLEH SUMBERDAYA MANUSIA PENDIDIKAN YANG BERMUTU - RUGAIYAH, RUGAIYAH (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2010)
Improving the quality ef education management begins with the improvement of human resources schools, principals as school managers need to have a high competence. To assume the principal's office is necessary to prepare the candidates who meet the qualifications and competence Goals of this study to obtain strategy to get quality education through ; first competency mapping pricipal candidate, second; competency mapping for the principal candidates in terms of the total competence of the principal, third competency mapping principal candidate from each principal aspects of competence. Surory approach use for this study data analysis with kuantitatif descriptive. Collecting data principal of competency with instmment by paper and pencil Result of this study to Mapping of Competence Principal Candidate, first Mapping competencies for prospective principals principals only 3% of the candidates included in the category of high competence, and 46% of the principal candidates have been category, 51 % belong to low or very low. Second mapping competencies of principal are acquired 63% of the principal candidates have mastered the managerial competence and social competence, for competence and personal entrepreneurship 4 3% of the principal candidates master the competence, the competence for supervision while the only 26% controlled by the principal candidate. Third Mapping competencies for managerial competence, entrepreneurship, personal, supervision and social, there are some competencies have mastery and any competece have not master. Based on mapping results, the implication of this study are : for the competence of managerial skills development priorities through education and training or workshop activities. For entrepreneurial competencies need to be trained to think of creative and innovative capabilities through case studies. For the supervision competencies need to be trained through simulation. For social competence and personality is only required to guide them through regular meetings. Keywords: Strategy, qualified human resources, headmaster competence-managerial personality-supervision-social entrepreneurship.